Studying the Antimicrobial Effects of Silver Nanoparticles Coated with Alginate Biosynthesized by Dulcicalothrix alborzica - Bahareh Nowruzi; Hassan Beyranvand (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: Nowadays, Cyanobacteria are one of the important candidates in the green biosynthesis of nanoparticles. Considering the detrimental effects of chemically synthesized nanoparticles, the aim of this study was the biosynthesis and antimicrobial activity of nanoparticles by aquatic cyanobacterium. Methods: Silver nanoparticles (AgNPs) were biosynthesized using three different approaches: wet biomass, boiling, and extracellular polysaccharides (EPS). Alginate coating was employed to enhance the nanoparticles' stability. Characterization of the nanoparticles was performed using UV-vis spectroscopy, Fourier transform infrared (FTIR) analysis, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and zeta potential measurements. The antimicrobial properties of the nanoparticles were evaluated against fish pathogenic bacteria and fungi. Statistical analyzes were performed with SPSS version 16 software, and the significant difference between the means was performed with one-way analysis of variance with 95% confidence limits and Tukey's test, and the results were drawn as a graph with Excel software. Results: The UV-vis spectroscopy results confirmed the synthesis of AgNPs in all three methods. FTIR analysis revealed similar spectra for all three methods, indicating comparable purity and production of similar compounds. Electron microscope images showed the sphericity of nanoparticles prepared by boiling method, and the average diameter of uncoated and alginate coated nanoparticles was 38 and 180.04 nm, respectively. Zeta potential analysis indicated a positive surface charge on the nanoparticles. The highest zone of inhibition was observed for AgNPs synthesized by the boiling method and coated with alginate. Similar results were obtained for the antifungal activity, with Saprolegnia exhibiting higher sensitivity to the synthesized nanoparticles compared to the other species studied. Conclusion: The novel strain Dulcicalothrix alborzica demonstrated potential as a potent producer of AgNPs with unique properties and promising applications in microbial biotechnology.